Around the World in Eighty Days - Verne, Jules (Lahore Readings, 2016)
In 1872 Phileas Fogg wins a bet by traveling around the world in seventy-nine days, twenty-three hours, and fifty-seven minutes.
Keywords: Fantasy fiction